SARS-CoV-2 infection in hemodialysis patients: Preliminary data from a Portuguese hospital center - Tavares,Joana (2020)
Background: In December 2019, a new form of coronavirus was identified (COVID-19) and quickly became a worldwide pandemic. Previous data reported a more severe disease in older patients, with high comorbidities, which are common features in hemodialysis patients. Scarce data is available about the clinical presentation and outcomes in this population. For this reason, we aim to report the characteristics of COVID-19 disease in hemodialysis patients admitted to our center. Methods: We retrospectively reviewed all patients on chronic hemodialysis admitted with a laboratory-confirmed COVID-19 infection from March 2nd to May 20th of 2020. Baseline characteristics, clinical, laboratory and radiological presentation were registered and treatment and outcomes Results: Fourteen patients were included, 57% female, with a median age of 81 years old and a high number of comorbidities. Cough and fever were the most common symptoms and lymphocytopenia, increased inflammatory parameters and coagulation dysregulation were frequently registered. Ground-glass opacities were present in each thorax computerized tomography performed. Five patients developed respiratory insufficiency, but none needed invasive ventilation or ICU admission. In a significant proportion, discharge was postponed due to the impossibility of ensuring social isolation. Median viral shedding was 38 days. Discussion and conclusion: Hemodialysis patients who required hospitalization were very old and had multiple comorbidities. Even so, the impaired immune response of this population seems to cause a less severe course of the disease and a longer time of viral shedding. HD units have required a reformulation of their circuits in order to avoid disease spreading.